The Influence of Sustainability Reporting, Big Data, IT Governance, and Gender Diversity on Firm Value in The Infrastructure Sector Listed on The Indonesia Stock Exchange period 2021-2024 - Rara Andini; Dirvi Surya Abbas; Imam Hidayat (LP2M IAIN Palopo, 2026)
This study examines the influence of Sustainability Reporting, Big Data, IT Governance, and Gender Diversity on firm value in infrastructure companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. A quantitative approach is employed using panel data collected from annual reports and financial statements. The sample is determined through purposive sampling based on predefined criteria. Data analysis is conducted using panel data regression, with model selection tests including the Chow Test, Hausman Test, and Lagrange Multiplier Test, which identify the Random Effect Model (REM) as the most appropriate model. The results indicate that, simultaneously, Sustainability Reporting, Big Data, IT Governance, and Gender Diversity have a significant effect on firm value. However, partially, only Gender Diversity shows a significant positive influence, suggesting that higher female representation in managerial positions enhances decision-making quality and increases investor confidence. In contrast, Sustainability Reporting, Big Data, and IT Governance do not show significant individual effects on firm value during the observed period. These findings imply that gender diversity plays a strategic role in improving firm value, while ESG disclosures and technological initiatives have not yet become key determinants of firm valuation in the infrastructure sector. Future research is recommended to include additional variables, longer observation periods, or different sectors to obtain more comprehensive insights.